Synchronization of GnRH and PGF2? on estrus response, pregnancy, progesterone hormones in crossing of Swamp Buffalo and Water Buffalo in West Sumatra, Indonesia - Elly Roza; SALAM N. ARITONANG; HILDA SUSANTI; AFRIANI SANDRA (Society for Indonesian Biodiversity, 2019)
Abstract. Roza E, Aritonang SN, Susanti H, Sandra A. 2019. Synchronization of GnRH and PGF2? on estrus response, pregnancy, progesterone hormones in crossing of swamp buffalo and water buffalo in West Sumatra, Indonesia. Biodiversitas 20: 2910-2914. This study aims to determine the effect of GnRH and PGF2? synchronization on estrus emergence, pregnancy percentage, progesterone hormone levels and blood profile from artificial insemination (AI) of swamp and water buffalo crossing in Sijunjung, West Sumatra. The samples were 21 female swamp buffaloes with criteria clinically healthy, age ? 2.5 years and not pregnant. All buffalos on the first day were synchronized using 250 ?gGnRH (Fertagyl®, Intervet International). All of the buffaloes received 12.5 ?g PGF2? on the seventh day after GnRH injection. On the second day after injection of PG2?, the observation of estrus was carried out, the buffalos with estrus symptoms appeared after performing AI for 18 hours which the estrus symptoms was seen using a 0.5 ml Murrah buffalo semen with a sperm concentration of 500 million. Blood serum of 3-5 ml for the examination of progesterone levels was taken on days 21, 24, and 27 after appeared in AI. Hormone analysis was performed using the Enzyme-Linked Immunoabsorbent Assay (ELISA) method. The variables measured were the percentage of estrus, pregnancy, progesterone hormone levels, and blood profile. Pregnancy examination (PE) was carried out after 90 days in AI through rectal palpation. The data were analyzed descriptively. The results showed synchronization of GnRH and PG2? hormones in buffalo cattle which had 100% estrus, 66.67% pregnancy after AI, pregnant buffalo progesterone concentration 5.09-8.87 ng/mL and non-pregnant 1.11-3.45 ng/mL, total blood protein 7.9 g/L and blood glucose 86.86 mg/dL. The conclusion of this study is that the combination of GnRH and PG2? gives a clear appearance of estrus, progesterone hormone levels, and optimal buffalo blood profile.